Astrakhan Persian Cultural Educational Society “Anjuman-Hairia” (1909-1911) - R. N. Pirova (Научный диалог)
The article is devoted to the history of the Persian cultural society Anjuman-Hairia functioned in Astrakhan in 1909-1911. It is noted that the growth of national consciousness of Russian Muslims in the early 20th century was marked by the creation of national and local organisations to develop a programme of ethno-confessional development, to formulate the main issues of cultural movement, etc. One such organization was intended to become Astrakhan Shiite society “Anjuman,” uniting the Turks of the Transcaucasia, subjects of the Russian and the Persian crowns. It is shown that the origins of its creation stood on the rich Shiite merchants who set general tone in the organization, repurposing it mainly for charity. It is stated that participation in the activities of the society of residents, who were Persian subjects, and of Persian Consul directly, determined rather complex perception of the organization by the Russian authorities in the period under review. Special attention is paid to the analysis of practical activities of the organization and the reasons that led to its closure. Through the involvement of archival sources and materials of periodicals of the early 20th century the author gives a comprehensive analysis of the main areas of activity, describes the specifics of the organizational forms of “Anjuman” society. The role of society in the development of Shiites’ primary education in Astrakhan outside the framework of confessional communities is emphasized.